A new Hermite – Hadamard type inequality and an application to quasi-Einstein metrics - Xiang Gao (Нелінійні коливання, 2014)
We firstly establish a new generalization of the classical Hermite – Hadamard inequality for a real-valued convex function. Then the convexity of the matrix function g(A) = f(det A) is proved under certain conditions on the function f and the matrix A. Based on these, we derive a new Hermite – Hadamard type inequality, and finally present an application to the estimate of the volume of quasi-Einstein metrics. Спочатку встановлено узагальнення класичної нерiвностi Ермiта – Адамара для дiйсної опуклої функцiї. Далi доведено опуклiсть матричнозначної функцiї g(A) = f(det A) за певних умов на функцiю f та матрицю A. На пiдставi цього результату отримано узагальнення нерiвностi типу Ермiта – Адамара та наведено застосування до оцiнки об’єму квазiейнштейнiвської метрики.